ANALISIS PENGARUH LITERASI KEUANGAN DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP PERILAKU KONSUMTIF MAHASISWA - H Hadiatullah; Nining Sudiyarti; K Kurniawansyah (Jurnal Ekonomi & Bisnis, 2023)
The purpose of this study was to know the effect of financial literacy and social economic status of parents on students’ consumptive behavior at students of economics and management faculty Samawa University, both partially and simultaneously. The data used in this study is quantitative data obtained directly from primary sources. The primary data used in this study were collected using a questionnaire. the population in this study were all students of the Faculty of Economics and Management, Samawa University in 2022, totaling 624 people. However, researchers did not conduct research on the entire population, researchers narrowed the population using the sampling method. To determine the number of samples, researchers used the Slovin formula. Based on the calculation results, the number of samples that will be used as respondents in this study is 95 people. All data were analyzed using multiple linear regression analysis techniques, partial hypothesis test (t test), simultaneous hypothesis test (F test), and determination coefficient test (R2). The results of the study showed that financial literacy and parents' socio-economic status have a positive and significant effect on the consumptive behavior of students of the Faculty of Economics and Management, Samawa University, both partially and simultaneously. The ability of financial literacy variables and parents' socioeconomic status to influence changes in student consumptive behavior variables is 58.3%, while the remaining 41.7% is influenced by other variables outside this research model, such as lifestyle, self-control, promotion, impulse buying, and social environment.